Early-onset restrictive cardiomyopathy with life-threatening arrhythmia caused by a homozygous desmin mutation: a case report - Tianjiao Wang; Weina Zhao; Lifang Wu; Qinlai Ying; Wen Zhu; Yiqun Teng; Xiaolin Liu (BMC Pediatrics)
Abstract Restrictive cardiomyopathy (RCM) is a rare cardiac disease characterized by the predominance of severe diastolic dysfunction, normal or mildly increased ventricular wall thickness, and either normal or mildly reduced ejection fraction. All known RCM genes are localized on autosomes. In most cases, the mutations are inherited in an autosomal dominant mode or appear as de novo mutations. The present report describes a case with early-onset RCM and life-threatening arrhythmia, which was inherited in an autosomal recessive manner. The child developed ventricular arrhythmia at one month of age, and a mixed phenotype dominated by restrictive cardiomyopathy with coexistent hypertrophic cardiomyopathy (RCM - HCM) at one year of age. and required hospitalization for anti - heart failure treatment due to heart failure at three years of age. The patient suffered from ventricular fibrillation and cardiac arrest at four years of age, which was rescued by extracorporeal membrane oxygenation and subsequent heart transplantation. Whole genome sequencing of the proband revealed a novel homozygous missense variant (NM_001927.3: c.1243 C > T [p.R415W]) in the Desmin (DES) gene, which was inherited from heterozygous unaffected parents. This case further expands our knowledge of desmin-related cardiomyopathy in children.